PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. POS INDONESIA (PERSERO) GRESIK - Danial Fariz; Mei Retno Adiwaty (REVITALISASI : Jurnal Ilmu Manajemen, 2021)
This study aims to determine the effect of work environment and labor discipline on job satisfaction of employees at PT. Pos Indonesia (persero) Gresik. The population of this study were all employees at PT. Pos Indonesia (persero) Gresik, which amounts to 63. The sampling technique used in this study used the saturated sampling method, information gathering is carried out throught distributing questionnaires to all employees. The analysis technique used in this study is to use the Partial Least Square (PLS) application with reliability test, validation tests, and hypothesis testing. Based on the results of the study, it was found that: 1) work environment has a contribution to job satisfaction, which means that the better the work environment in a company, the better the job satisfaction in the company. 2) Labor discipline has a contribution to job satisfaction, which means that the better labor discipline the better the job satisfaction. The company needs to improve the work environment and the labor discipline given to employees so that employee job satisfaction increases